2006
DOI: 10.1063/1.2369628
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of Pt∕PbTiO3∕PbZr0.3Ti0.7O3∕PbTiO3∕Pt integrated capacitors etched in noncrystalline phase

Abstract: Uniformly patterned Pt∕PbTiO3∕PbZr0.3Ti0.7O3∕PbTiO3∕Pt capacitor arrays were etched in noncrystalline phase. The ferroelectric layer was well crystallized and contains uniform grains. The capacitors exhibit well-saturated hysteresis loop and excellent fatigue properties in terms of larger saturation polarization Pmax of 53.2μC∕cm2 at an applied voltage of 12V, higher remnant polarization Pr of 30.5μC∕cm2 for a coercive field of 58kV∕cm, remnant polarization of about 81.2% at 1010 switching cycles, and a low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The details of the typical integrated process and the innovated integrated process were given elsewhere. 1,2,10) The sandwich structure ferroelectric thin films PbTiO 3 /PbZr 0:3 Ti 0:7 O 3 /PbTiO 3 (PT/ PZT/PT) were deposited by sol-gel method. 11) The ferroelectric capacitors fabricated by the typical integrated process and the innovated integrated process are denoted by ''TIP-FeCAP'' and ''IIP-FeCAP'', respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the typical integrated process and the innovated integrated process were given elsewhere. 1,2,10) The sandwich structure ferroelectric thin films PbTiO 3 /PbZr 0:3 Ti 0:7 O 3 /PbTiO 3 (PT/ PZT/PT) were deposited by sol-gel method. 11) The ferroelectric capacitors fabricated by the typical integrated process and the innovated integrated process are denoted by ''TIP-FeCAP'' and ''IIP-FeCAP'', respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, dry etching has become one of the critical processes for the pattern transfer in Si integrated circuit devices. 1,2) The ferroelectric films are very sensitive to high density plasma occurring during dry etching process, and giving rise to the degradation of the electrical properties because of physical damage and chemical residue contamination in the etchingdamaged surface layers and side wall of ferroelectric capacitors. [3][4][5][6] Therefore, the investigating etching damage and the understanding degradation of electric properties in ferroelectric thin films are very important.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt/PT/PZT/PT/Pt capacitors were integrated by an innovative process. Details of the processing and properties of the capacitor are given elsewhere [8,9,14].…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported an innovative ferroelectric capacitor integrated process [8,9]. The investigation of the properties of the Pt/PbTiO 3 /PbZr 0.3 Ti 0.7 O 3 /PbTiO 3 /Pt (Pt/PT/PZT/PT/Pt) capacitor indicated that the etch damage was minimized by the innovative process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PZT properties are influenced by fabrication processing, especially plasma etching [135][136][137][138][139][140][141][142][143][144]. Nowadays, with the decreasing of device feature size, plasma etching (or dry etching) is more widely used than wet etching, because of its an-isotropic and accurate pattern transfer for PZT [145]. The further development of RF-MEMS switches application requires an increased integration density.…”
Section: Chaptermentioning
confidence: 99%